Systematic Notes on the Genus Claassenia Wu (Plecoptera: Perlidae), with Description of a New Species - Stark, Bill P. (Illiesia, 2010)
Claassenia drukpa sp. n. is described from Bhutan, a lectotype is designated for C. manchuriana (Banks) and it is placed as a synonym of C. radiata (Klapálek). Claassenia semibrachyptera Wu & Claassen is redescribed from the holotype and paratype specimens in the United States National Museum and the egg of Claassenia sabulosa (Banks) is redescribed from scanning electron micrographs. Four additional Asian species are described under informal designations.
Keywords: entomologija; entomology; new species; nove vrste; Claassenia; Slovenia; Plecoptera